2019
DOI: 10.1007/jhep03(2019)079
|View full text |Cite
|
Sign up to set email alerts
|

Towards a full solution of the large N double-scaled SYK model

Abstract: We compute the exact, all energy scale, 4-point function of the large N doublescaled SYK model, by using only combinatorial tools and relating the correlation functions to sums over chord diagrams. We apply the result to obtain corrections to the maximal Lyapunov exponent at low temperatures. We present the rules for the non-perturbative diagrammatic description of correlation functions of the entire model. The latter indicate that the model can be solved by a reduction of a quantum deformation of SL(2), that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
287
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(298 citation statements)
references
References 66 publications
(238 reference statements)
11
287
0
Order By: Relevance
“…It would be very significant if we can find the exact eigenvalue density ρ(E). It is argued in [46,47] that the eigenvalue density of the SYK model is closely related to the q-Hermite polynomials. It would be interesting to see if the double scaling limit of the q-Hermite polynomials has some connection to the exact eigenvalue density ρ(E) of the JT gravity case.…”
Section: Discussionmentioning
confidence: 99%
“…It would be very significant if we can find the exact eigenvalue density ρ(E). It is argued in [46,47] that the eigenvalue density of the SYK model is closely related to the q-Hermite polynomials. It would be interesting to see if the double scaling limit of the q-Hermite polynomials has some connection to the exact eigenvalue density ρ(E) of the JT gravity case.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting direction is to study the role of q-deformations for the 2d gauge theory associated to a non-compact group, which have played an important role in the case of compact groups [72]. Such a deformation is also relevant from the boundary perspective, where [73] have shown that correlation functions in the large-N double-scaled limit of the SYK model can be described in terms of representations of q-deformed SU (1, 1).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…There has been a recent explosion of interest in the so-called Sachdev-Ye-Kitaev models, see e.g. [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17]. These 0+1d quantum models of all-to-all interacting fermions contain 1+1d gravitational features such as black holes and chaotic behavior.…”
mentioning
confidence: 99%